Perbandingan Hasil Radiografi Efusi Pleura Pada Proyeksi Right Lateral Decubitus (RLD) Dan Left Lateral Decubitus (LLD) Pada Klinis Dengue Haemoragic Fever (DHF) Di RSU. Wisata Universitas Indonesia Timur - Akhmadi Akhmadi; Rini Hatma Rusli; Muhamad Rudiansyah; Amelia Niwele; Yohannes Hursepunny (Universitas Muhamadiyah Manado, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can be fatal in a relatively short time. This disease is classified as